2005
DOI: 10.1063/1.1923175
|View full text |Cite
|
Sign up to set email alerts
|

Green emission from Er-doped GaN powder

Abstract: Green light emission has been directly obtained from Er-doped GaN powder. Er is incorporated into GaN powder through the reaction between molten (Ga+Er) and NH3 at 950–1050°C using Bi as a wetting agent. Photoexcitation with an Ar laser results in strong green emissions from two narrow lines at 537 and 558nm, which are identified as Er transitions from the H11∕22 and S3∕24 levels to the I15∕24 ground state. Microprobe analysis reveals that Er atoms are distributed across powder particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Recently, various groups have demonstrated activator emission in bulk GaN powders. Blue emission was demonstrated by Ogi et al with their GaN:Mg powders [6], while green emission from Er 3+ activated GaN powders was observed by Wu et al [7]. Nyk et al also showed Eu 3+ and Tb 3+ emission separately in GaN host [8].…”
mentioning
confidence: 90%
“…Recently, various groups have demonstrated activator emission in bulk GaN powders. Blue emission was demonstrated by Ogi et al with their GaN:Mg powders [6], while green emission from Er 3+ activated GaN powders was observed by Wu et al [7]. Nyk et al also showed Eu 3+ and Tb 3+ emission separately in GaN host [8].…”
mentioning
confidence: 90%
“…The first report of RE:GaN powder [3] showed green emission similar to bulk RE:GaN grown by Steckl and Zavada [1,2]. Interest in RE:GaN powder has increased due to the demonstration of RE:GaN powder based thin film transistors (TFT's), success in incorporating red light emitting Eu centers in GaN matrix and demonstration of its complementary metal oxide semiconductor (CMOS) compatibility [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large size mismatch between Ln 3+ and Ga 3+ , it is however very difficult to incorporate lanthanide ions inside a GaN matrix and this might be the reason that there is not much literature available on lanthanide-doped GaN nanomaterials. [27][28][29][30] Though the incorporation of Eu 3+ and Er 3+ ions into nanopowders of GaN leads to red and green emissions, respectively, blue emission is challenging since there are hardly any reports on the incorporation of the corresponding Ln 3+ ions like Dy 3+ and Tm 3+ into GaN nanoparticles or nanopowders. This could be due to the presence of these lanthanide ions near the surface which are subsequently quenched by surface defects or by adsorbed organic moisture (e.g., H 2 O).…”
Section: Introductionmentioning
confidence: 99%